Pengaruh Minat Penggunaan Payment Quick Response Code Indonesian Standard (QRIS) terhadap Masyarakat di Kota Ternate - Situru, Agatha Christy; Malik, Mahardika Catur Putriwana (Jurnal Manarang Manajemen dan Bisnis, 2023)
The purpose of this research is to find out the interest in using the Payment Quick Response Code Indonesian Standard (QRIS) for the people in Ternate City. The casual study analysis method becomes a method in this study by using a quantitative approach. The perceived benefits gained by using QRIS can improve job performance by making digital payments efficient and effective.The perception of security that exists in using QRIS makes someone want to use it in a cash payment system for non-cash payments because apart from the benefits you get there is also the perceived security in using the technology.